Development of green transportation system - Rahman, Mohammed Ataur; Ahmed, Helmi; Rafia, Afroz; Alam, A. H. M. Zahirul; Rashid, Muhammad Mahbubur (2013)
The incomplete combustion of automobiles and light-duty trucks engines causes the green house gas (GHG) emissions. The GHG emission can be reduced by developing energy efficient transportation system driven by electrical motor powered by battery. A dynamic model has been developed to define the total power requirement of the vehicle for the battery power pack selection. A green transportation system driven by an AC induction motor powered by LiFePO4 battery has been developed from this study to contribute on reduction of green house gas emission. The high acceleration periods of the green transport (EV) needs powerful electrical currents, causes temperature spike of the cells of LiFePO4. The cell temperature spike is due to internal resistance and electrochemical reaction which causes the battery performance decline. The operating temperature of the LiFePO4 batteries needs to maintain in the range of 25-40C. The evaporative cooling thermal management system has been developed for the proposed transportation system which has supported the tested car to travel 69 km with maintaining the battery temperature in the range of 20-40C.